Indonesian Moderate Islam: A Constructivist Approach to Global Perceptions - Haqqi, Halifa (Faculty of Law, Universitas Pekalongan, 2023)
This study explores the construction of Moderate Islam in Indonesia and its significance for both national identity and foreign policy. As part of its strategic positioning, Indonesia actively promotes itself as a Moderate Muslim nation to counter radicalism and extremism, aligning this narrative with its commitment to tolerance and democracy. Employing a qualitative descriptive approach within a constructivist framework, this research examines policy documents, academic studies, and governmental reports to analyze the roles of state and non-state actors—including Muhammadiyah, Nahdlatul Ulama, and the Ministry of Foreign Affairs—in shaping and advancing the discourse of Moderate Islam through multi-track diplomacy. The findings indicate that Moderate Islam in Indonesia is not a static or preordained identity but rather an evolving construct shaped by historical, political, and sociocultural interactions. A paradox emerges as the state’s official narratives often fail to align with social realities, particularly concerning issues of intolerance and discrimination. The instrumentalization of Moderate Islam for political purposes raises critical concerns regarding inclusivity and representation. This study contributes to constructivist international relations theory by demonstrating how religious norms influence state behavior and shape diplomatic engagement. It further argues that policy reforms are necessary to bridge the gap between diplomatic rhetoric and domestic realities, ensuring that the discourse on Moderate Islam functions not only as a strategic tool of soft power but also as an authentic reflection of societal values.